MODIFIED APPROACH USING LSB IN IMAGE STEGANOGRAPHY - Kaur, Navjot; Singh, Manpreet (International Journal of Research -GRANTHAALAYAH, 2015)
Steganography is a profession of masking the secret information using some other harmless message. One needs to be very careful while sharing any information on public network as there are more chances of an intrusion. Therefore the art of covering information is highly in demand known as Steganography. To satisfy the need of safe transmission, many known techniques like modern data compression, information theory, spread spectrum, and cryptography technologies were integrated to bring up Steganography. This paper proposed an approach of building a secure data hiding technique using Cryptography and Steganography which assures high secrecy of data over network.